Compression and heat transfer properties of porous copper structure from investment casting - Choy, Zhi Jian (2016)
Copper was important to the early ages of life and it will continue to be the material of choice for a variety of applications such as domestic and industrial [1]. Presently, copper is used for telecommunications, heating and cooling systems and power generation. This research project seeks to find a novel method to design and perform the fabrication of porous metal, namely copper. In the fabrication of the porous copper, certain limitations were met as a number of methods used were unsuccessful. However, using investment casting through 3D printed mould proved successful. Different pore sizes and shapes of the porous copper were manufactured where the compression strength and heat transfer properties were tested. It was found that the heat transfer properties were better for smaller pore sizes of the fabricated sample. The heat transfer coefficient increases with decreasing pore sizes. Square shaped pores are seen to be the most efficient in convective heat transfer. Compression tests done on the fabricated samples have found the porous copper of higher porosity have higher energy absorption but exhibits lower stress as compared to those with lower porosity. Circular pores are found to be superior in mechanical properties such as the modulus of elasticity and possess high energy absorption. This final year project will provide insights on the various fabrication techniques that are used for making the porous copper, and also evaluation on the various thermal and physical properties of the porous copper. Lastly, this final year project seeks to provide a better platform for future projects to work on.